2020
DOI: 10.7717/peerj.9253
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent theta burst stimulation facilitates functional connectivity from the dorsal premotor cortex to primary motor cortex

Abstract: Background Motor information in the brain is transmitted from the dorsal premotor cortex (PMd) to the primary motor cortex (M1), where it is further processed and relayed to the spinal cord to eventually generate muscle movement. However, how information from the PMd affects M1 processing and the final output is unclear. Here, we applied intermittent theta burst stimulation (iTBS) to the PMd to alter cortical excitability not only at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…It was reported that when this intensity was applied directly over M1, it did not influence M1 excitability (Huang et al., 2009). Given that the present study identified the location of PMd similarly to previous studies (Huang et al., 2009, 2018; Meng et al., 2020), it is therefore unlikely that M1 was directly activated during PMd iTBS.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It was reported that when this intensity was applied directly over M1, it did not influence M1 excitability (Huang et al., 2009). Given that the present study identified the location of PMd similarly to previous studies (Huang et al., 2009, 2018; Meng et al., 2020), it is therefore unlikely that M1 was directly activated during PMd iTBS.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with existing literature, iTBS consisted of bursts of three pulses given at a frequency of 50 Hz. Each triplet was repeated 10 times at 200 ms within a 2 s train, and this was repeated every 8 s for 20 cycles, totalling 600 pulses (Huang et al., 2005 , 2008 , 2018 ; Meng et al., 2020 ). The location of left PMd was defined as 8% of the distance between the nasion and inion (∼2.5–3 cm) anterior to the M1 hotspot, consistent with previous work (Huang et al., 2018 ; Koch et al., 2007 ; Meng et al., 2020 ; Münchau et al., 2002 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reaction time acceleration following anodal tDCS was found independent of the task (random vs. sequential) suggesting an unspecific stimulation effect. A comparable effect has been shown for the implicit task variant [61] and may occur due to an excitatory effect of anodal tDCS on corticospinal excitability as has been shown for TMS [76,77] yielding a beneficial effect on task performance. The data are summarized in Figure 5.…”
Section: Reaction Times During Srtt Trainingsupporting
confidence: 63%